Construção coletiva de experiências inovadoras no processo ensino-aprendizagem na formação de profissionais da saúde - Ferreira, Maria De Lourdes Da Silva Marques [UNESP]; Cotta, Rosângela Minardi Mitre; Oliveira, Marilda Siriani De (Associação Brasileira de Educação Médica, 2009)
This study analyzes from the perspective of health education the production of a group of tutors in the forum about the distance specialization course Activation of change processes in the higher education of health professionals, that took place in June-August/2005, under the sponsorship of the Ministry of Health, Fiocruz and Rede Unida as a result of the practice report entitled when the question qualifies the view. The objective was to analyze the collective production of the forum regarding the discussion of the following questions: How was the concept of care built historically from the different professions and kinds of knowledge? How should we deal with a focal (innovative) teaching-learning experience? How can innovative governability/feasibility be ensured within the context of management? These questions were formulated by the group during the in-person meeting whose initial question was: What should be changed to change? The methodology used was the technique of qualitative interpretation of the collective subject speech based on the theoretical referential of Lefréve.

Sob a perspectiva do ensino e saúde, este trabalho analisa a discussão realizada durante o processo de formação de um grupo de tutores no fórum do curso de especialização em Ativação de processos de mudança na formação superior de profissionais de Saúde, no período de junho a agosto de 2005, promovido pelo Ministério da Saúde do Brasil, Fiocruz e Rede Unida, resultante do processamento do relato de prática, intitulado Quando a pergunta qualifica o olhar. O objetivo foi analisar a produção coletiva do fórum na discussão das seguintes questões, elaboradas pelo grupo durante o encontro presencial: Como se deu historicamente a construção do conceito de cuidado a partir dos diferentes saberes-profissões?; Como lidar com uma experiência focal (inovadora) de ensino-aprendizagem?; Como garantir a governabilidade-viabilidade inovadora no contexto da gestão? A questão de aprendizagem inicial foi: o que mudar para fazer a mudança? Utilizou-se como metodologia a técnica de interpretação qualitativa do discurso do sujeito coletivo, a partir do referencial teórico de Lefréve, Lefréve e Teixeira (2000).
Collective construction of innovative experiences in the teaching-learning process of health professionals
Keywords: Collective construction; Learning; Methodology; Collective subject; Delivery of health care; Health personel; Construção coletiva; Aprendizagem; Metodologia; Sujeito coletivo; Cuidados de saúde; Pessoal e saúde